Determination of Heat Transfer Coefficient for an Interaction of Sub-cooled Gas and Metal - Mohd Zaidi, Sidek (IOP Publishing, 2016)
Heat transfer coefficient (HTC) for a hot metal surface and their surrounding is one of the need be defined parameter in hot forming process. This study has been conducted to determine the HTC for an interaction between sub-cooled gas sprayed on a hot metal surface. Both experiments and finite element have been adopted in this work. Initially, the designated experiment was conducted to obtain temperature history of spray cooling process. Then, an inverse method was adopted to calculate the HTC value before we validate in a finite element simulation model. The result shows that the heat transfer coefficient for interaction of subcooled gas and hot metal surface is 1000 W/m2K.